2015
DOI: 10.5586/asbp.2015.022
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous steroid hormones stimulate full development of autonomous endosperm in Arabidopsis thaliana

Abstract: Most flowering plants, including important crops, require double fertilization to form an embryo and endosperm, which nourishes it. Independence from fertilization is a feature of apomictic plants that produce seeds, from which the plants that are clones of the mother plant arise. The phenomenon of apomixis occurs in some sexual plants under specific circumstances. Since the launch of a fertilization-independent mechanism is considered a useful tool for plant breeding, there have been efforts to artificially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Application of selected estrogens on Arabidopsis plants grown on artificial medium [15], winter wheat [33], sage (Salvia splendens) [34] and chicory (Cichorium intybus) [14] was found to stimulate flowering. More recently, it was reported that in vitro culture of unpollinated Arabidopsis pistils on media supplemented with estrone and progesterone resulted in the development of autonomous endosperm [35].…”
Section: Growth and Developmentmentioning
confidence: 99%
“…Application of selected estrogens on Arabidopsis plants grown on artificial medium [15], winter wheat [33], sage (Salvia splendens) [34] and chicory (Cichorium intybus) [14] was found to stimulate flowering. More recently, it was reported that in vitro culture of unpollinated Arabidopsis pistils on media supplemented with estrone and progesterone resulted in the development of autonomous endosperm [35].…”
Section: Growth and Developmentmentioning
confidence: 99%
“…At the same time, the role of plant hormones in promoting the differentiation of adventitious buds has been elucidated through tissue culture techniques. Under the stimulation of exogenous steroid hormones (estrone, androsterone, progesterone and epibrassinolide), Arabidopsis thaliana can complete the development of endosperm without fertilization (Rojek et al 2015). So it can be inferred that hormones also play important roles in the apomixis.…”
Section: Molecular Study Of Apomixismentioning
confidence: 99%
“…Some families naturally show particularly high frequencies of apomixis, examples are: Poaceae (Sharma et al 2014;Boldrini et al 2006;Hojsgaard et al 2008;Albertini et al 2005;Niemann et al 2012), Asteraceae (Whitton et al 2008;Hand et al 2015), Rosaceae (DOBEŠ et al 2015;Burgess et al 2014) and Melastomataceae (Mendes-Rodrigues and Oliveira 2012; Maia et al 2016). In 1986, Richards counted known apomictic species, finding more than 300 taxa, distributed over 35 families (Richards 1986). Today, according to incomplete statistics, plants found to have apomictic reproductive ability exceed 400 genera (Grimanelli et al 2003;Koltunow and Grossniklaus 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutation of the POLYCOMB REPRESSIVE COMPLEX 2 ( PRC-2 ) genes in Arabidopsis confers a degree of haploid embryo development ( Guitton and Berger, 2005 ) and/or autonomous endosperm development ( Ohad et al ., 1996 , 1999 ; Kiyosue et al , 1999 ; Luo et al , 1999 ; Vinkenoog and Scott, 2001 ). Autonomous endosperm can also be induced in wild Arabidopsis genotypes and other taxa within the Brassicaceae using chemical agents in vitro ( Rojek et al ., 2005 , 2013 , 2015 ; Kapusta et al , 2007 ; Figueiredo et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%